Implications of Electronic Money on the Potential of Israf and the Formation of Syariah Consumption Behavior - Rizamatun Nikmah; Mufidatul Himmah (Anjasmoro: Islamic Interdisciplinary Journal, 2026)
This study aims to analyze the implications of electronic money on the potential of Islamic teachings (Israf) and the formation of sharia consumption behavior among students of SMKN 01 Sempol. This study uses a quantitative approach with a causal associative research design. Data were collected through the distribution of Likert -scale questionnaires to 30 respondents selected using purposive sampling techniques . Data analysis was performed using simple linear regression through two equation models with the help of SPSS. The results of the study indicate that the use of electronic money has a positive and significant influence on the potential of Israf, as evidenced by the regression coefficient of 0.675 and a significance level of 0.000. In addition, the use of electronic money also has a positive and significant influence on the formation of sharia consumption behavior with a regression coefficient of 0.731 and a significance level of 0.000. The coefficient of determination shows that the Electronic Money variable explains 67.2% of the variation in Israf Potential and 49.6% of the variation in sharia consumption behavior. The findings of this study indicate that electronic money has complex characteristics. On the one hand, it can improve transaction efficiency, but on the other hand, it has the potential to encourage excessive consumption (Israf). Therefore, it is necessary to strengthen Islamic financial literacy and self-control so that the use of electronic money remains in line with Islamic consumption principles.